Pengembangan Wisata Pesisir Berkelanjutan di Kabupaten Rembang - Yusuf, Irfan Murtadho; Kismartini, Kismartini; Nurul Huda, Mohammad (Asosiasi Ilmuwan Administrasi Negara (AsIAN), 2024)
Coastal tourism as a form of natural tourism has a very promising development in Indonesia, but unfortunately it is not accompanied by ecological maintenance. Several coastal tourist destinations have experienced a decline in ecological quality, such as the problem of waste that is not managed properly and seawater pollution due to activities on land. The purpose of this study was to analyze whether the development of Karangjahe Beach tourism is in accordance with the principles of sustainable development (Economic Sustainability; Ecology Sustainability & Social Sustainability). The research method used is descriptive qualitative with primary data collection techniques through interviews and Focus Group Discussions, while secondary data is obtained from electronic mass media, previous research results and from related agency report documents. The results of the study indicate that Karangjahe tourism in terms of economic sustainability has been able to provide economic benefits to both the local community and regional income, in terms of Environmental Sustainability the tourist destination is able to change the coastal conditions to be greener, while in terms of social sustainability it is shown from the manager's concern in maintaining local culture. There are several weaknesses in each of these sustainability parameters, so it can be said that the achievement of sustainability has not been optimally achieved. Therefore, it is recommended to the local government and to the managers of tourist destinations to pay more attention to all aspects of sustainability.